1989
DOI: 10.1203/00006450-198903000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Defective Leukocyte Fungicidal Activity in End-Organ Resistance to 1,25-Dihydroxyvitamin D

Abstract: ABSTRACT. Recent studies have shown 1,25(OH)zD~ receptor-mediated modulation of leukocyte proliferation, differentiation, and function. We examined the phagocytosis and killing of microorganisms by neutrophils and monocytes from five patients of three families with hereditary resistance to 1,25(OH)2D3. Phagocytosis of microorganisms by patients' neutrophils and monocytes was normal. However, defective neutrophil killing activity toward Candida albicans (30-40% of controls) was found in all patients. The killin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…1,25D enhances the protective effects of the innate immune response. Individuals who are vitamin D deficient [ 60 ] and those with inactivating mutations in the gene encoding VDR show defects in responses towards infectious agents [ 61 ]. Tiosano and colleagues examined the immune status of fifteen hereditary vitamin-D resistant patients that have a truncated VDR, which is unable to bind 1,25D and devoid of function.…”
Section: 1α25-dihydroxyvitamin D 3 and Anticanmentioning
confidence: 99%
“…1,25D enhances the protective effects of the innate immune response. Individuals who are vitamin D deficient [ 60 ] and those with inactivating mutations in the gene encoding VDR show defects in responses towards infectious agents [ 61 ]. Tiosano and colleagues examined the immune status of fifteen hereditary vitamin-D resistant patients that have a truncated VDR, which is unable to bind 1,25D and devoid of function.…”
Section: 1α25-dihydroxyvitamin D 3 and Anticanmentioning
confidence: 99%
“…Patients with loss-of-function VDR mutations provide the ultimate tool to understand the importance of the VDR, and over the years many of the extra-intestinal claims attributed to vitamin D were examined. Etzioni et al [21], the consulting pediatric immunologist at our institute, showed that other than slightly impaired phagocytosis and Candida killing, the immune system functions normally in the absence of VDR effect. Endocrine glands, including the pancreatic β-cell, respond normally to routinely used stimuli, provided that serum calcium is normal [22].…”
Section: Introductionmentioning
confidence: 99%
“…137 In animal studies, Cantorna et al 138 demonstrated that 1,25-D 3 may reduce the prevalence of opportunistic infections such as candidiasis. metabolism and precluding this crucial step.…”
mentioning
confidence: 99%